PENGARUH INSENTIF TERHADAP KINERJA KARYAWAN DENGAN VARIABEL INTERVENING MOTIVASI KERJA PADA PT GANDA MADY INDOTAMA - Alfarizi, Achmad; Suharini, Suharini; Hastasari, Ratih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Incentives are needed to improve the motivation and performance of employees to always work optimally, so that the vision and mission of the organization / company can be achieved. This research aims to explain: 1) The Effect of Incentives on Employee Work Motivation; 2) Influence of Employee Performance Incentives; 3) The Effect of Work Motivation on Employee Performance, 4) The Significance of Work Motivation as an intervening between incentives and employee performance. This Explanatory Research conducted with a quantitative approach, using Regression-path analysis and Sobel analysis. The data used are primary data, obtained through online questionnaires (google form) as many as 30 samples which is the total population of outsourced employees of PT. Ganda Mady Indotama in the Pondok Labu AL-Izhar school area numbered 30 people. Variabels studied include Incentives, Work Motivation and Employee Performance. The results of the path analysis showed that the Incentive variabel (X) had a significant effect on Work Motivation (Y1) with a beta value of 0.677, the Incentive variabel (X) significantly affected Employee Performance (Y2) with a beta value of 0.279, the Work Motivation variabel (Y1) significantly affected Employee Performance (Y2) with a beta value of 0,650. Work motivation is proven to be variabel intervening in the relationship between the influence of incentive variabels on employee performance. The total effect of Incentives on Employee Performance through Work Motivation increased to 0.719. But its influence as an intervening is not significant because the p-value of the Sobel test of 0.071 is greater than 0.05. Keyword: path analysis, incentives, work motivation, employee performance, intervening variabels